(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This research paper, derived from the author’s Ph.D. thesis, explores the linguistic and curriculum challenges faced by educators teaching students of the Brogpa tribe in Ladakh, India. The Brogpa community, known for its distinct cultural and linguistic heritage, presents unique educational barriers, particularly in language accessibility and curriculum relevance. Through a descriptive research approach, data was collected from 51 teachers across four Brogpa villages, highlighting the impact of language barriers, curriculum inadequacies, and socio-economic factors on student engagement. Findings reveal that a majority of teachers emphasize the necessity of Brogpa teachers to bridge the linguistic divide. Additionally, the study uncovers challenges such as lack of parental support, irregular attendance, and limited infrastructure, further exacerbated during the COVID-19 pandemic due to poor internet connectivity and restricted access to digital learning tools. The research suggests integrating bilingual education, culturally relevant curriculum modifications, enhanced teacher training, and improved infrastructure to foster an inclusive and effective learning environment for Brogpa students. Addressing these issues through community engagement and policy adaptations can significantly improve the quality of education in tribal regions.